2012
DOI: 10.1063/1.4736863
|View full text |Cite
|
Sign up to set email alerts
|

A finite-difference time-domain simulation of high power microwave generated plasma at atmospheric pressures

Abstract: A finite-difference algorithm was developed to calculate several RF breakdown parameters, for example, the formative delay time that is observed between the initial application of a RF field to a dielectric surface and the formation of field-induced plasma interrupting the RF power flow. The analysis is focused on the surface being exposed to a background gas pressure above 50 Torr. The finite-difference algorithm provides numerical solutions to partial differential equations with high resolution in the time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The high-power microwave (HPM) has important applications in military and civilian fields, such as directed energy weapons, creation of artificial plasma mirrors, long distance wireless energy transport, and so on. [1] In recent years, the peak electric field of the HPM has reached several MV/m, [2,3] which is close to or exceeds the gas breakdown threshold at high pressures. Once the gas breakdown occurs, the generated plasma strongly hinders the radiation and propagation of the HPM.…”
Section: Introductionmentioning
confidence: 98%
“…The high-power microwave (HPM) has important applications in military and civilian fields, such as directed energy weapons, creation of artificial plasma mirrors, long distance wireless energy transport, and so on. [1] In recent years, the peak electric field of the HPM has reached several MV/m, [2,3] which is close to or exceeds the gas breakdown threshold at high pressures. Once the gas breakdown occurs, the generated plasma strongly hinders the radiation and propagation of the HPM.…”
Section: Introductionmentioning
confidence: 98%
“…[1] In recent years, the electric field radiated from the aperture antenna reaches several MV/m that can exceed the breakdown electric field at atmospheric pressure. [2,3] Once the air breakdown occurs, the attendant plasma strongly hinders the microwave radiation. This suggests that the radiated power reaches the maximum (or critical) value when the maximum electric field in the near-field region is equal to the breakdown electric field.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have studied the air breakdown caused by the high-power microwave. [7][8][9][10] Nam et al introduced the pressure-independent enhanced electron energy distribution function into the global model, and improved fidelity for modeling the gas breakdown. [7] The twodimensional model coupling Maxwell equations with plasma fluid equations was developed by Boeuf et al to simulate the patterns of breakdown plasma, in which the accurate diffusion coefficient was adopted.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Ford et al used the finitedifference time-domain method to solve a one-dimensional model similar to that of Boeuf et al, and predicted the breakdown formation time and the microwave transmission in the breakdown plasma. [9] The Poisson and Boltzmann equations were utilized by Zhu et al to describe the air breakdown near the dielectric window, and the results showed that the range can be roughly divided into at least two regions, sheath region and plasma region. [10] Most of these studies above focused on the case in which the microwave has one electric field com-ponent or two mutually orthogonal and inphase electric field components.…”
Section: Introductionmentioning
confidence: 99%